Moving on trial: protocol for a pilot randomised controlled trial of models of housing and support to reduce risks of COVID-19 infection and homelessness - Randell, Elizabeth; Pell, Bethan; Moody, Gwenllian; Dyer, Calie; Smallman, Kim; Hood, Kerenza; White, James; Aubry, Tim; Culhane, Dennis; Hume, Susannah; Greaves, Faye; Rodriguez-Guzman, Guillermo; et al. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background It is estimated that around 160,000 households in Britain experience homelessness each year, although no definitive statistics exist. Between March and September 2020, as part of the initial ‘Everyone In’ government response to COVID-19 in England, 10,566 people were living in emergency accommodation and nearly 18,911 people had been moved into settled accommodation. However, some forms of temporary accommodation may not be suitable as shared facilities make it impossible for people to adhere to government guidelines to reduce the spread of COVID-19. Methods This is parallel group, pilot randomised controlled trial. The target is to recruit three local authorities, each of which will recruit 50 participants (thus a total of approximately 150 participants). Individuals are eligible if they are aged 18 and over, in a single-person homeless household, temporarily accommodated by the LA with recourse to public funds. Participants will be randomised to receive settled accommodation (intervention group) or temporary accommodation (control group). The intervention group includes settled housing such as Private Rented Sector (low and medium support), Social Housing (low and medium support), and Housing First (High support). The control group will maintain treatment as usual. The follow-up period will last 6 months. The primary outcome is to assess the feasibility of recruitment, retention, and acceptability of trial processes against progression criteria laid out in a traffic light system (green: all criteria are met, the trial should progress as designed in this pilot; amber: the majority of criteria are met and with adaptations to methods all criteria could be met; red: the minority of criteria are met and the pilot RCT should not proceed). Secondary outcomes include assessment of completeness of data collection at 3 and 6 months and percentage of participants consenting to data linkage, as well as a process evaluation and economic evaluation. Discussion This trial will address feasibility questions associated with progression to a fully powered effectiveness trial of models of housing to reduce risk of COVID-19 infection and homelessness. Trial registration ISRCTN69564614 . Registered on December 16, 2020.